The Economic Importance of Interconnection of Investment and Innovation Processes - Muminovna, Malikova Dilrabo; A. S., Ubaydullayev (Journal of Innovation in Education and Social Research, 2024)
The interrelation between investment and innovation processes is a crucial aspect of economic development and growth. Investment plays a vital role in fostering innovation by providing the necessary financial resources for research, development, and implementation of new ideas, technologies, and products. The paper discusses the essence, types and necessity of investments, as well as innovation activities. Moreover, the article presents the relationship between investment and innovation activities.